Situation Report: Czechoslovakia, 4 February 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Husak Becomes National Front Chairman Czech Union of Scientists Abolished The Czechoslovak-Soviet Friendship Society Trade Agreements with Yugoslavia and Romania